Improving Learning Outcomes Through The Science Technology Society (STS) Learning Model Based On Project Methods - Ivayuni Listiani; Pinkan Amita Tri Prasasti (Department of Biology Education, Faculty of Education and teacher Training, Maritime University of Raja Ali Haji, 2021)
Science learning should be learned by following the nature of science, which refers to the learning process, from the process of learning processed in such a way as to produce products, attitudes, and technologies used by students as a means to improve cognitive, affective, and psychomotor abilities. The observations showed that science learning is less inviting students to find and address problems in society, as a result of students' attitudes towards the environment less, and the learning outcomes obtained by students are also low. Therefore, there is a need for learning activities that can empower the learning process by using the project-based Science Technology Society (STS) learning model. The purpose of this study is 1) knowing the implementation of the syntax of project-based STS learning model in students of the Elementary School Teacher Education Study Program Semester 7 academic year 2019/2020 FKIP Universitas PGRI Madiun in environmental pollution material, 2) knowing the improvement of learning results. This research is a class action study, conducted in three cycles consisting of the stage of planning, implementation, observation, and reflection. Validation of research is done by the triangulation method. Cognitive learning data collection techniques using tests, affective learning results using observation sheets and polls, and psychomotor learning results using observation sheets and tests. Data analysis using qualitative and inference analysis techniques. Concluded in the study namely: 1) STS learning model has been implemented well by STS syntax: problem orientation, concept formation, concept application, concept strengthening, and assessment in students of Elementary School Teacher Education Study Program Semester 7 academic year 2019/2020 FKIP Universitas PGRI Madiun environmental pollution material, 2) there is an increase in student learning outcomes in cognitive, affective, and psychomotor aspects.